2019
DOI: 10.1055/s-0039-1693706
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria in Cystic Fibrosis

Abstract: Over the past decade, the incidence of nontuberculous mycobacterial (NTM) infection has been increasing in cystic fibrosis patients. Along with this have come a host of complications and burdens to patients that threaten longevity and quality of life. The two main constituents of NTM pulmonary disease, Mycobacterium avium complex (MAC) and M. abscessus, are notoriously difficult to treat with suboptimal clinical responses and are accompanied by high treatment burdens for patients. This review aims to summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 141 publications
(137 reference statements)
1
24
1
2
Order By: Relevance
“…Mabc is a subspecies of the Mabc complex that includes Mabc, M. massiliense, and M. bolletii, and has major clinical implications due to antibiotic resistance [2,3]. Mabc often causes pulmonary infection in patients with immune deficiencies, such as cystic fibrosis; however, it can also threaten immunocompetent individuals [4,5]. Mabc is divided into two morphological types, smooth and rough variants, depending on the colony phenotype [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Mabc is a subspecies of the Mabc complex that includes Mabc, M. massiliense, and M. bolletii, and has major clinical implications due to antibiotic resistance [2,3]. Mabc often causes pulmonary infection in patients with immune deficiencies, such as cystic fibrosis; however, it can also threaten immunocompetent individuals [4,5]. Mabc is divided into two morphological types, smooth and rough variants, depending on the colony phenotype [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 5–20% of CF patients will develop NTM infection (Richards and Olivier, 2019 ), indicating that these patients are at increased risk of infection due to genetic susceptibility. Although less frequently encountered than M. avium or M. abscessus , several studies have reported the presence of M. fortuitum in CF patients (Sermet-Gaudelus et al, 2003 ; Cândido et al, 2014 ; Martiniano et al, 2016 ; Richards and Olivier, 2019 ). Recent work has shown that CFTR is important for fine-tuning host oxidative stress and restricting intracellular growth of M. abscessus in a zebrafish model (Bernut et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…They have emerged in recent years as prevalent pathogens in cystic fibrosis (CF) patients, with several global CF centers reporting the isolation of NTM in the respiratory tract of CF patients (Roux et al, 2009;Skolnik et al, 2016). NTM prevalence in CF patients varies between 5 and 20%, with the Mycobacterium avium complex and the Mycobacterium abscessus complex being the most significant species (Richards and Olivier, 2019). However, less frequently isolated species in CF patients include other NTM, such as Mycobacterium gordonae, Mycobacterium kansasii or M. fortuitum (Sermet-Gaudelus et al, 2003;Cândido et al, 2014;Martiniano et al, 2016;Richards and Olivier, 2019 Wallace, 2002;Brown-Elliott and Philley, 2017;Tortoli et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we explore the interaction of Ag85 with Fn at the single molecule level. We concentrate on M. abscessus, an emerging, human-transmissible, multidrug-resistant pathogen causing severe lung infections in cystic fibrosis patients, often resulting in poor treatment outcomes [27,28]. Like other nontuberculous mycobacteria, M. abscessus presents as two different morphological forms, i.e., a smooth (S) morphotype characterized by smooth, dome-shaped, mucoid colonies and homogenously dispersed liquid cultures, and a rough (R) morphotype characterized by rough, dry, wrinkled colonies and highly aggregated liquid cultures [29].…”
Section: Introductionmentioning
confidence: 99%